REDUCING ENERGY CONSUMPTION OF BARKWOOD WASTE GRINDING ON EQUIPMENT WITH KNIFE-BASED OPERATIONAL UNITS - Kunickaya, Ol'ga; Zhuk, Artem; Nikiforova, Valentina; Chzhan, Svetlana; Gorodnichina, Mariia; Runova, Elena; Garus, Ivan; Ivanov, Viktor (Journal of Applied Engineering Science, 2020)
In the coming decades, wood waste management for biofuel production is regarded as a promising renewable energy source and a key factor in reducing carbon dioxide emissions. Mechanical grinding is seen as one of the main techniques in wood waste pre-treatment operations that increases the value of feedstock used for fuel. The application potential of the ground product highly depends on the energy efficiency of the process. This work aimed to establish a consistent pattern for estimating the energy consumption required for grinding spruce and pine barking waste depending on the degree to which materials are ground and their relative moisture content. The energy consumption parameters at grinding were analyzed employing three grinding energy models of Rittinger, Kripichev-Kik, and Bond. The results of estimation showed that specific energy consumption is associated with relative moisture content and the grinding degree by nonlinear dependence according to the Kripichev-Kik grinding model for spruce and pine bark. It has been established that the specific energy consumption at grinding spruce and pine barking waste at the optimum humidity of 25% and 27%, respectively, is proportional to the natural logarithm of the grinding degree. It was concluded that the wood waste grinding by 5–15 times requires higher energy consumption at optimum moisture content, which is 5–10% and 7–14% of the heating value for spruce and pine, respectively. The knowledge acquired through this research will contribute to developing possible approaches for wood waste recycling in a more energy-efficient way.